2017
DOI: 10.1007/s12020-017-1393-3
|View full text |Cite
|
Sign up to set email alerts
|

The roles of microRNA-34b-5p in angiogenesis of thyroid carcinoma

Abstract: miR-34b-5p functions as a potent regulator of angiogenesis, apoptosis and cell proliferation via modulation of VEGF-A, Bcl-2 and Notch1 proteins. It could be a target for developing treatment strategies of thyroid carcinoma with aggressive clinical behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
2
20
1
Order By: Relevance
“…Additionally, genetic and epigenetic abnormalities in different molecules and growth factors have also been reported as risk factor in thyroid carcinogenesis. Among these growth factor, vascular endothelial growth factor (VEGF) is an important factor, encoded by the VEGF proto-oncogene (VEGF/VEGF-A), and is activated in hypoxic intracellular environments (Maroof et al, 2017). A subfamily of growth factors, VEGF-A acts as the main ligand that induces VEGFR-1 and VEGFR-2, the primary receptor involved in tumour angiogenesis (Holmes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genetic and epigenetic abnormalities in different molecules and growth factors have also been reported as risk factor in thyroid carcinogenesis. Among these growth factor, vascular endothelial growth factor (VEGF) is an important factor, encoded by the VEGF proto-oncogene (VEGF/VEGF-A), and is activated in hypoxic intracellular environments (Maroof et al, 2017). A subfamily of growth factors, VEGF-A acts as the main ligand that induces VEGFR-1 and VEGFR-2, the primary receptor involved in tumour angiogenesis (Holmes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…4a). Interestingly, previous articles reported that miR-34b-5p regulates multiple cellular processes including cell apoptosis and cell proliferation through participating in a several critical signal pathway like VEGF-A, BCL2 and Notch [28]. To determine the interaction between BCL2 and miR-34b-5p, wild type 3'UTR (containing miR-34b-5p recognition site) and the mutant 3'UTR of BCL2 were cloned into luciferase reporter plasmids.…”
Section: Linc02418 Acts As a Cerna For Mir-34b-5p In Crc Cellsmentioning
confidence: 99%
“…4a). Interestingly, previous articles reported that miR-34b-5p regulates multiple cellular processes including cell apoptosis and cell proliferation through participating in a several critical signal pathway like VEGF-A, BCL2 and Notch [28]. To determine the interaction between BCL2 and miR-34b-5p, wild type 3'UTR (containing miR-34b-5p recognition site) and the mutant 3'UTR of BCL2 were sub-cloned into luciferase reporter plasmids.…”
Section: Knockdown Of Linc02418 Inhibits Tumor Growth Cell Mobility mentioning
confidence: 99%